1995
DOI: 10.1523/jneurosci.15-03-02186.1995
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of putative D4 dopamine receptors in postmortem striatum from patients with schizophrenia

Abstract: The identification of five dopamine receptor subtypes has given the dopamine hypothesis of schizophrenia new life. The D4 receptor is particularly intriguing because it binds clozapine with high affinity. Putative D4 receptors were labeled in postmortem human brain by subtracting the binding of a saturating concentration of 3H-raclopride (6 nM, which labels D2 and D3 receptors) from that labeled by a saturating concentration of [3H]YM 0915–2 (1–1.3 nM, which labels D2, D3, and D4 receptors). In the control bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
0
1

Year Published

1996
1996
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(94 citation statements)
references
References 28 publications
4
87
0
1
Order By: Relevance
“…
Using an indirect subtraction binding technique and human postmortem tissue, several laboratories [1][2][3] reported finding increases in dopamine D 4 receptors in caudate nuclei of schizophrenic patients, although others [4][5][6] have not replicated these findings. NGD-94-1 is a selective D 4 antagonist with low affinity for the D 2 and D 3 receptors.
…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…
Using an indirect subtraction binding technique and human postmortem tissue, several laboratories [1][2][3] reported finding increases in dopamine D 4 receptors in caudate nuclei of schizophrenic patients, although others [4][5][6] have not replicated these findings. NGD-94-1 is a selective D 4 antagonist with low affinity for the D 2 and D 3 receptors.
…”
mentioning
confidence: 99%
“…Recently, using an indirect binding technique, increases in the dopamine D 4 receptor density had been reported [1][2][3] in schizophrenic subjects but replication of this finding was not always possible. [4][5][6] This indirect method consists of subtracting the density found with the D 2 The discovery of NGD-94-1, which is a selective dopamine D 4 receptor antagonist, 7,8 has provided the opportunity to study D 4 receptor densities in a direct manner.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Much effort has now gone into this task. Recently, Murray et al (1995) have replicated this finding in brains from drug-treated patients using quantitative receptor autoradiography but the elevation (two-fold) was more modest. Estimating very low abundance receptors by subtracting two estimates of very high abundance receptors is clearly prey to artefact.…”
Section: Update On Post-mortem Studiesmentioning
confidence: 88%
“…41 In diseased postmortem human tissue, several studies using such radioligand binding methods reported significantly higher D 4 receptor-density in CPu tissue from subjects diagnosed with schizophrenia than in normal controls. [36][37][38] Again, others failed to replicate these findings. 40,42,43 A recent analysis with the D 4 -selective radioligand [ 3 H]NGD 94-1, detected no changes in radioligand binding in postmortem CPu tissue from brains of normal controls and patients with schizophrenia.…”
Section: Expression Of Brain D 4 Receptor Mrnamentioning
confidence: 99%